RISK FACTORS OF STRESS AND HISTORY OF ALLERGY TO DYMENORRHEA IN ADOLESCENT STUDENTS IN PUBLIC MIDDLE SCHOOL 1 PASIKOLAGA: Allergy to Dysmenorrhea - Sinarning Sinarning; Tasnim Tasnim; La Banudi (STIKes Mandala Waluya Kendari, 2022)
Background: The prior study for 20 students in Public Middle School 1 Pasikolaga showed that 16 students (32.8%) experienced dysmenorrhea, 3 students (1.46%) often experienced dysmenorrhea and 1 student never experienced dysmenorrhea. The objective of this study was to analyse the risk factor of stress and history of allergy to dysmenorrheal in adolescent students in Public Middle School 1 Pasikolaga. Methods: Quantitative research with analytical method with case control study design. The research location is Public Middle School 1 Pasiokolaga, Muna Regency, Southeast Sulawesi. The population of all students from class VII to class IX is 205. The number of samples is 134 with a sampling technique usingstratified random sampling. Result: The results of data analysis obtained the value of Odds Ratio (OR) = 1.568, this means that stress with the incidence of dysmenorrhea has a 1.56 times greater risk of developing dysmenorrhea compared to respondents who do not have stress and the value of Odds Ratio (OR) = 1.459, this means history of allergy with dysmenorrhea has a risk of 1,459 times the occurrence of dysmenorrhea compared to respondents who do not have a history of allergies. Conclusion: Stress and history of allergies are risk factors for the incidence of dysmenorrhea in public of female students1 Pasikolaga.